Teachers’ Techniques in Teaching English to Young Learners - St. Hartina (Institut Agama Islam Negeri Palopo, 2019)
The objectives of this research were to find out the teachers’ techniques in teaching, the problems in teaching and the best teaching techniques used by the teacher in teaching English to young learners at TK Bambini School of Makassar. It applied descriptive qualitative research. The subjects of the research were three kindergarten teachers of TK Bambini School of Makassar. The data were obtained through interview and observation. The data were analyzed based on procedure of data analysis that consisted of the data collection, the data reduction, the data display, and conclusion: drawing/verification. The findings showed that (1) the teachers’ techniques in teaching English to young learners were singing a song, games, presentation practice and production, drilling, demonstration, story-telling, reading aloud, and dictation, (2) the teachers’ problems in applying the certain teaching techniques were learners’ lack of self-confidence, learners’ uncontrollable movement when singing and playing the games, learners’ misunderstanding towards the games rules and the story, learners’ less focus on teachers’ presentation and instructions, learners’ unfamiliarity of the spelling words, learners’ inability to read and write the word or sentences, and the teachers’ difficulty in explaining the lesson and in performing science experiment, (3) the best teaching techniques implemented by the teachers were playing games, demonstration and presentation practice and production.